Pemilihan Siswa Terbaik Menggunakan Simple Addictive Weighting pada SMK Assalam Depok - Kusmanto, Tria Hadi; Hatmoko, Bondan Dwi (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
This research aims to develop a Best Student Selection System using the Simple Additive Weighting (SAW) method. Problem identification was carried out through observation and interviews with individuals authorized to manage and understand the best student selection process at SMK Assalam. A literature review was conducted to gather information about the SAW method and its application in schools. The alternative data collected included ten students selected as candidates for the selection process, which was then normalized to convert the data into a relative and comparative scale across criteria. The decision support system implemented using the SAW method was evaluated by collecting implementation data and analyzing the results. The evaluation results indicate that the system can provide useful information to support decision-making in selecting the best student.